Resistance Characteristics of Soil Fertility - Alfiani, Nofita; L, Koddam Rukadi; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Fertile soil is an important indication to support plant growth. The more fertile a soil then plant growth, the better. In this study, the method used is to measure the resistance of different types of fertilizer are manure, compost. Because different forms of land then the resistance will also vary according to the shape of the land. The results obtained are cage fertilizer that has the smallest resistance is 39.7 ? and 33.6 ? whereas compost and 35.4 ? 41.9 ?. The benefits of this method were to determine the resistance or resistance from the ground. So the lower the ground obstacles, the more fertile the land. Conversely, the higher the resistance of the soil, the more the soil is not fertile.